A qualitative exploration of healthcare workers' perspectives on and experiences with colorectal cancer screening in the Western and Eastern Cape - Payne, Alexandra (Department of Public Health and Family Medicine, 2026)
In South Africa (SA), colorectal cancer (CRC) incidence and mortality is growing at an alarming rate. CRC is often diagnosed at an advanced stage in SA with a noted increase in younger diagnoses and poor outcomes. However, CRC screening and specifically faecal immunochemical testing (FIT) is not currently offered in the public healthcare sector in SA. Before implementing any sort of screening test, it is important to address health system related factors that are specific to the South African context to better understand the potential feasibility and acceptability of a screening test. To establish a foundation for the potential implementation of a FIT screening program, this qualitative study aimed to explore primary and secondary healthcare workers' perceptions of CRC screening. Materials and Methods: The PRECEDE portion of the PRECEDE-PROCEED model, which identifies predisposing (intrapersonal), reinforcing (interpersonal) and enabling (structural) constructs within the context of health behaviours, served as the theoretical framework for this study. Eight healthcare providers (n=6 physicians and n=2 nurses) practicing in both the Western and Eastern Cape were purposively sampled to participate in semi-structured qualitative interviews. Interviews were analysed using thematic analysis guided by the model. Results: Perceived barriers to CRC screening were identified as socioeconomic status, work status and personal discomfort with tests (predisposing); geographical challenges and healthcare worker related factors (reinforcing); and pathology lab services, test costs, lack of proper ablutions, and lack of clinical continuity and communication (enabling). Perceived facilitators were identified as health education (predisposing); primary care physicians' training in CRC risk and testing location (reinforcing); and test affordability, communication across different health systems, and test availability at primary care level (enabling). Conclusion: This study identifies context specific perceived barriers and facilitators among primary and secondary healthcare workers to CRC screening in South Africa. If CRC FIT screening were to be implemented in SA, relevant policy makers and stakeholders would need to address these perceived barriers across multiple levels.